THE INFLUENCE OF BRAND AMBASSADOR AND KOREAN WAVE ON PURCHASE DECISION FOR NEO COFFEE PRODUCTS - Lutfia Siskhawati; Hutomo Atman Maulana (Jurnal Ekonomi Dan Bisnis, 2021)
This research was conducted to determine the influence of brand ambassadors and Korean wave on purchasing decisions for Neo Coffee Products. The population in this research are all the people who have bought Neo Coffee product in Riau Province. Samples in this research were taken by using purposive sampling method that consist of 100 respondents. This research used multiple linear regression as data analysis technique. The result showed that brand ambassador did not have significant effect on purchasing decisions partially (t=1.176, p=0.243), Korean wave have a positive and significant effect on purchasing decisions partially (t=8.265, p=0.000), and  simultaneously, brand ambassador and Korean wave have a positive and significant effect on the decision to purchase Neo Coffee products (F=75.841, p=0.000, R2=0.61)